Volume-dependent catalytic efficiency of highly durable Au@Ag–Pt core@multi-shell nanoparticles in methylene blue reduction - Lee, Hu-Jun; Dao, Anh Thi Ngoc; Kaneko, Kenji (Royal Society of Chemistry, 2025)
Monodispersed spherical Au@Ag–Pt core@multi-shell nanoparticles were synthesized using a co-reduction method that integrates galvanic replacement with a versatile reducing agent. Their nanostructure was thoroughly characterized using scanning transmission electron microscopy and energy-dispersive X-ray spectroscopy. The average diameter of the Au core was 18 nm, while the Pt granules within the shell region measured approximately 2.1 nm, with the Ag–Pt shell having an average thickness of 3.3 nm. The catalytic activity of these nanoparticles was evaluated by the reduction of methylene blue dye in the presence of NaBH4, monitored by ultraviolet-visible spectrophotometry. The mass-to-charge ratio peaks of the reduced dye were further quantified using electrospray ionization mass spectrometry. A representative pseudo-first-order rate constant of 5.924 min−1 was calculated. Moreover, the nanoparticles maintained over 99% catalytic efficiency even after six consecutive cycles of methylene blue reduction and after six months of storage, with no significant changes in their nanostructure. These results demonstrate the nanoparticles' excellent stability, reusability, and durability. Therefore, Au@Ag–Pt core@multi-shell nanoparticles synthesized via this co-reduction approach show strong potential for practical applications in wastewater treatment involving azo dye reduction.